A comparison of the effectiveness of the aspartat aminotransferase enzyme (AST) between the hypothermia and the normal state in the liver and blood of Syrian hamsters (Journal of Hama University, 2022)
The effect of hypothermia on the enzymatic activity of the aspartate aminotransferase enzyme AST was studied on 32 animals of Syrian hamsters of average 7-9 months and weighing between (90-120) g. The Syrian hamster or the golden hamster (Mesoicetusauratus) belongs to the rodent family and has unique anatomical and physiological characteristics that make it a desirable research model. It is generally very hard and easy to tame animal, and males are more docile and easier to handle.The results of the study during the normal state showed that the activity of the AST enzyme in the liver was directly proportional to the increase in temperature. In the blood serum, the results showed that there wasn't significant effect of temperature on the activity of the studied enzyme in the normal state. While the activity of AST in the blood serum was significantly reduced compared to that of the liver, Where  as the effectiveness in the liver reached at 15 ° C (61 µm/g/h)  While in the blood recorded (0,48 µm/ml/h)which indicates a decrease in the level of the enzyme in the serum.The results of the study showed that during the hypothermia, the activity of AST enzyme in the liver reached its peak at 37 °C for the brooding medium, which is the same temperature as the hamster's body temperature.The results of the study also showed a decrease in the activity of the enzyme in the liver in the case of hypothermia where recorded (99 µm/g/h) compared with its activity in the normal condition where recorded (323 µm/g/h) at the same temperature. While in the blood there was a significant  increase in the activity of the enzyme AST in the case of hypothermia compared with its activity in the normal condition.